2015
DOI: 10.1074/jbc.m115.653584
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 Stabilizes the Tight Junction Protein Occludin and Protects Intestinal Epithelial Barrier Function

Abstract: Background: Prolyl hydroxylases (PHDs) are linked to inflammatory bowel diseases (IBD); however, the exact role of PHD3, a member of PHD family, in IBD is unknown. Results: Deletion of Phd3 in mice intestinal epithelial cells causes spontaneous colitis. Conclusion: PHD3 protects the intestinal epithelial barrier function. Significance: The results are helpful for the development of therapeutic strategies for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 51 publications
6
39
0
Order By: Relevance
“…Previous studies have indicated a potential linkage between genetic mutations or deletions in tight junctionassociated proteins and development of IBD [45]. Further studies also have proven that stabilizing junctional complex in intestinal barrier could attenuate intestinal inflammation [46]. In this paper, tight junction proteins claudin-5 and ZO-1 were notably downregulated in mice after DSS treatment, and further H&E identically supported our findings, indicating the impairment of intestinal mucosal barrier in DSS-induced colitis mice.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have indicated a potential linkage between genetic mutations or deletions in tight junctionassociated proteins and development of IBD [45]. Further studies also have proven that stabilizing junctional complex in intestinal barrier could attenuate intestinal inflammation [46]. In this paper, tight junction proteins claudin-5 and ZO-1 were notably downregulated in mice after DSS treatment, and further H&E identically supported our findings, indicating the impairment of intestinal mucosal barrier in DSS-induced colitis mice.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, HIF-1α is critical for 86). Interestingly, the expression of these enzymes was reported to be altered in inflammatory bowel disease, where the intestinal barrier is significantly perturbed (85)(86)(87). In keratinocytes, loss of PHD2 alters cell migration and subsequent wound healing in a HIF-dependent manner (88).…”
Section: Hif In Adaptive Immunitymentioning
confidence: 99%
“…While our understanding of the role of HIF hydroxylases in the regulation of immune cell function is far from complete, recent studies investigating individual HIF hydroxylase isoforms in discreet immune and epithelial cell subtypes have identified isoform-specific roles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Notably, these phenotypes are not fully accounted for by downstream HIF-dependent effects, further supporting the existence of alternative hydroxylase-regulated pathways such as NF-κB in immune cells.…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
“…It has previously been suggested that PHD3 is associated with the local tissue hypoxia that accompanies tumorigenesis, and may act as a tumor suppressor (18). Chen et al (19) demonstrated that PHD3 protected the intestinal epithelial barrier from ulcerative injury, which is one of the causes leading to the development of gastric cancer. However, although the actions of PHD3 in the suppression of angiogenesis, growth and differentiation of tumor cells have previously been reported (20), the detailed molecular mechanisms implicating PHD3 in gastric cancer have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%